Recent Publications (Quarterly Journal of Economics, 1949)
Recent Publications Get access The Quarterly Journal of Economics, Volume 63, Issue 3, August 1949, Pages 435–437, https://doi.org/10.1093/qje/63.3.435 Published: 01 August 1949